Influencing Factors in Adopting TQM at Benghazi University-Libya - Yousef M. T. Al-Qumati; Ali M. A. Al-Hashemi (University of Science and Technology, Yemen, 2014)
Influencing Factors in Adopting TQM at Benghazi University-Libya Abstract:  Higher education inLibyareached to low standards of TQM, as affirmed in numerous studies and national human development report, the results show that among the most important problems lies in the low standard of educational administration and a lack of quality standards in education. Researchers find that a side from the problem of higher education is an administrative problem, and that the administration is the most important cause in of the development and quality of education. The study aims to determine the factors affecting the possibility of adopting TQM at theUniversityofBenghaziand measure the degree of availability of the elements of this approach in the management of the university. Researchers used the questionnaire as an instrument to collect the data that is necessary for the practical side. A number of about (110) were selected randomly of deans and heads of academic departments and the departments of public administration managers. Reliability coefficient was calculated in the questionnaire and descriptive statistics is used to identify trends participants, as well factor analysis to determine the factors for the adoption of TQM at theUniversityofBenghazi. The results of the study show that the factors affecting the possibility of adopting TQM from the point of view of participants, are not suitable for adoption in the management and university faculties, and that is due to inappropriate organizational environment, which is not conducive to the adoption of the principles and philosophy of TQM focusing on university mission, participate in decision-making, administrative decentralization, the use of the scientific method to solve problems, evaluation , continuous training and organizational culture. The study concluded that the factors of policies and procedures, organizational environment and evaluation are the most influential factor in the adoption of TQM. Keywords: Higher Education, Libya, the overall quality at the University of Benghazi, educational management, organizational structure.